THE EFFECT OF NON-MUSLIM COMMUNITY’S PERCEPTION ON INTEREST IN BECOMING SYARIAH BANK CUSTOMERS IN THE CITY OF BEKASI, WEST JAVA - Muhammad Rafi Aziz; Atiyah Fitri; Muhammad Doddy AB (Jurnal Ekonomi dan Perbankan Syariah, 2020)
This study aims to determine whether the cognitive perception, affective perception, and conative perception variables affect the people’s interest to become customers of Islamic banks in Bekasi City. It uses quantitative methods. As it uses the Slovin formula, the number of respondents was 100 out of a total population of 320,984 non-Muslim community in Bekasi City. The data analysis in this study adopted Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach and the data was processed using PLS 3.0. Based on the results of the data analysis, cognitive variables and affective variables do not have a significant effect on the people’s interest in becoming customers of Islamic banks in Bekasi City, while the conative variables have a significant effect on the people’s interest in becoming customers of Islamic banks in Bekasi City.